The Popularity of Asian Drama Series on Malaysian Television - Yoke Ling, Loh; ., . (International Journal of Engineering and Technology, 2018)
The Asian drama series has reached high popularity level among local viewers since this popular culture has penetrated into our local entertainment industry.Â The scheduling of the government or the private television stations specific to Asian drama series has increased when the response is very encouraging from the local viewers.Â Viewers are an important commodity in the capitalist system whereby when a cultural product obtains high viewing rating, automatically the popularity is also going to be high.Â Thus, for these Asian dramas series to achieve popularity, they need to draw the interest and demand of viewers in this region, where it can be explained through the concept of regionalization. Regionalization gives the priority to the psychology and phenomenon about the cultural approach and the cultural discount. This concept justifies the phenomenon of Asian drama series popularity in the Asian region.Â Â The content analysis and interview have been used in this study to analyze the elements contained in the Asian drama series, and whether or not they contribute to their popularity also perspective from local drama producers towards this phenomenon.Â Similarities in terms of the theme, characterization and narratives contained in the popular Asian drama series in this current work are the method and approach adopted in this work to reduce the cultural discount whereby through this similarity it has started to build the identity and characteristics of the Asian drama series seen as accepted and welcome by Asian viewers- something which is known as the cultural approach. The outcome of the study also shows that from the mainstream theme, good scripts, the right choice of artists and appropriate theme songs in the drama that they contribute to high popularity and altogether leave an impact to the Malaysian TV industry. Producers are in full authority not only in executive work but also in terms of the creativity.Â Â The decision made by a producer of a drama is vital to render a drama series a success. Â